The Development of Problem Based Learning Modules of Acid Base Materials in SMA N 5 Jambi in Developing Student Metacognitive Skills - Pauline Dewi Triani; Nazarudin Nazarudin; M Rusdi (Jurnal Pendidikan Kimia (JPKim), 2017)
Abstract: This research was motivated by the successful development of modules that serve as self-learning material for students, but the previous development of article the modules only show tasks in the form of multiple choice questions and essay. While there are so many types of tasks in the form of problems that can be used to improve student learning. This research goal was to understand how to develop module based on problem-based learning which are efficient and beneficial for the students, to analyse the application of problem-based learning modules on acid-base materials, and to understand the impact of problem-based learning modules to improve students' metacognition skills.This research used ADDIE development model consist of analysis, design, development, implementation, and evaluation. The data obtained from each stage of the ADDIE development model in the form of qualitative data were described. These were obtained from expert validators students and teachers. The problem based learning module developed by the researcher has been validated by two expert validators. The results from a small group trial showed that the students were able to follow each stage contained in modules well and was able to increase their metacognition skills using this module.Keywords: modules, problem-based learning, metacognition